ACCESSING SUSTAINABLE LINK AMID ACCESS TO ELECTRICITY CONSUMPTION AND LABOR FORCE PARTICIPATION RATE IN SOUTH AFRICA - Ahmed Oluwatobi ADEKUNLE (Association of Social and Educational Innovation, 2023)
Labor force participation rate is a strong issue that affect the performance of any economy including South Africa. Sequel to this, this paper accesses the link amid access to electricity consumption and labor force participation rate of male (LFPRM) in South Africa. Using yearly data from 1991- 2020. The study employed ARDL technique to evaluate the data. The findings of the study shows that access to electricity consumption (AEC) positively stimulate labor force participation rate of male in the long run while gross domestic product per capita growth impacted negatively on LFPRM in the short-run. The paper recommends that government should ensure that access to electricity consumption is improved and efficient in South Africa in order to boost LFPRM.